Role of residual stresses on fracture properties of under-matched butt weld - Rak, Inoslav (Kovine zlitine tehnologije, 1999)
Under-matched weld joints were adopted for producing a penstock of 47 mm wall thickness and 4200 mm diameter, to improve the weldability. The isothermal Robertson wide plate test on the under-matched weld joints, were the allowable stress level was 0.6 of the yield stress, proved that the longitudinal stresses caused the crack propagation alog the weld joint to deviate into tough base material where it was arrested. The arrest temperature was between -10 and -20°C. The behaviour of the crack propagation was the reason to omit the thermal stress relieving of the pipe section and on circumferential weld joints executed on this side. One can always take into consideration the role of axial residual stresses when assessing whether to use, or not, under-matched weld joints in severer loaded structures.
Keywords: zvari; napetosti; mehanske lastnosti; lomna žilavost